Acupuncture for psoriasis: protocol for a systematic review - Lei Wang; Weiming Wang; Haoyu Yang; Nuo Li; Yanping Bai (BMJ Open)
Introduction The described systematic review aims to assess the effectiveness and safety of acupuncture for psoriasis.Methods and analysis We will electronically search for randomised controlled trials in the following databases from inception to 31 March 2015: OVID MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Chinese Biomedical Literature Database, Chinese Medical Current Content, Chinese Scientific Journal Database (VIP database), Wan-Fang Database and China National Knowledge Infrastructure. We will also try to obtain literature by manually searching reference lists, conference proceedings and registers of clinical trials (eg, the Meta Register of Controlled Trials and the Chinese Clinical Trial Registry). Changes in disease status as evaluated by clinical signs or any available tool will be measured as the primary outcome. Global changes as well as changes in participant status (as evaluated by quality of life), safety (as measured by the prevalence and severity of adverse effects or adverse events) and costs (if available) will be measured as secondary outcomes. Two researchers will independently undertake selection of studies, data extraction and assessment of the quality of included studies. Data synthesis and subgroup analyses will be performed using special software (Review Manager). Data will be combined with a random effect model. Results will be presented as risk ratios for dichotomous data and the standardised mean difference for continuous data.Ethics and dissemination Ethical approval will not be required as this is a protocol for a systematic review. The systematic review will evaluate the current evidence regarding acupuncture therapy for psoriasis. Findings will be disseminated through peer-reviewed publications and conference presentations.Trial registration number PROSPERO CRD 42014013695.